The Correlation between Students’ Motivation in Learning English and Their English Learning Achievement at 2nd Grade Students of MA Hidayatul Mubtadi’in Lowokwaru Malang - Anike Nur Witasari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Motivation is the important thing for better achievement in studying English. The aim of this study is to figure out the correlation between students’ motivation and their English learning achievement at Madrasah Aliyah Hidayatul Mubtadi’in Lowokwaru Malang. The researcher collected the data from questionnaire and documentation, then analyzed the data through percentage of questionnaire using Pearson product moment coefficient of correlation SPSS 20. This study involved 43 students of second grade Madrasah Aliyah Hidayatul Mubtadi’in Lowokwaru Malang. The findings of this research showed that the descriptive statistics analysis of motivation score of the participants, the maximum score is 69, and minimum score is 40; the mean of the motivation score is 54.81. For English learning achievement, the maximum score is 100, and the minimum score is 35, the mean of the English learning achievement score is 72.79. The relationship is showed by the .669 Pearson correlation, which is significant at the .05 level, where it is higher than the .301 correlations coefficient table. This indicated that the null hypothesis is rejected and the alternative hypothesis is accepted. In conclusion, the correlation coefficient showed that there was significant relationship of both variables. There is a correlation between students' motivation and their English learning achievement. From the statistics above show that motivation is very influential for 2nd grade students of Madrasah Aliyah Hidayatul Mubtadi’in Lowokwaru Malang. It means that they had a pretty good motivation to learn, but still need for development in order to reach optimal learning results. Keywords: correlation, motivation, English learning achievement.